The Association between Locus of Control and Job Satisfaction to Auditor Ethical Sensitivity - Adi Gunawan; Munari Munari (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2019)
This study aims to analyze the association between locus of control and job satisfaction to auditor ethical sensitivity. The association between locus of control and ethical sensitivity is based on the notion that auditors with an internal locus of control likely have a high ethical sensitivity. The association between job satisfaction has emerged from the understanding that auditors who are satisfied with their jobs tend to have keen ethical sensitivity. The population of this study is 300 government auditors at the office of Financial and Development supervisory agency (BPKP) in East Java. The sampling technique is simple random sampling, which includes a minimum number of sample of 30 auditors. The type of data is primary data gathered from distributed questionnaires. Rank Spearman correlation test is used to determine the association between the variables. This research found that locus of control is related to auditor ethical sensitivity. It implies that internal locus of control can influence the auditors' decision-making when faced with an ethical dilemma. On the other hand, job satisfaction does not associate with auditor ethical sensitivity.